(untitled) (Revista Justiça do Direito, 2019)
The Rule of Law has relied on important institutes of this new time, such as the political representation, the mechanisms for controlling legislative production, the political parties and the liberalism as the ideology of the market, proposing the breaking of arbitrariness and the promotion of equality - even if initially only formal - and freedom - above all individual. This paper is about common issues of the rule of law, as the salvationist populism and rhetoric as an alternative to permanent fear and characteristics of fascism and its practical adoption by populism.